Human Papilloma Virus: Molecular Study in Congolese Women in the Departments of Niari and Bouenza - Boumba, Luc Magloire Anicet; Nganga, Parfait Christy; Ngatali, Sidney Frousse Christian; Loubano-voumbi , Ghislain; Moukassa, Donatien (New Horizons in Medicine and Medical Research Vol. 5, 2022)
Background: Human papillomaviruses (HPV) are the cause of many mucosal, benign, and malignant skin pathologies. Some so-called high-risk genotypes, particularly types 16 and 18, are implicated in the development of cervical cancer, one of the most common cancers in women. Objective: To determine the prevalence of HPV infections and to identify oncogenic genotypes circulating in the departments of Niari and Bouenza. Materials and Methods: A total of 207 cervical samples were analysed between 2019 and 2020. All samples were subjected to cervico vaginal smears for cytological investigation, and HPV DNA detection and genotyping were carried out using GeneXpert. Results: The average age of the women who participated in this study was 43.67±12.31 years in Niari and 38.29 ± 10.52 in Bouenza with age intervals ranging from 18 to 80 years. The following prevalences were discovered by cytological investigation of these samples: : Normal diagnosed in 89.58% (186/207) cases, ASCUS in 5.31% (11/207) cases, LSIL in 2.89% (6/207) cases, and ICC in 1.93% (4/207) cases. The prevalence of HPV infection was detected in 83.54% (66/186) of women without lesions, 6.32% (5/11) of ASCUS women and 10.12% (8/10) of women with cytological abnormalities [5.06% (4/6) LSIL, and 5.06% (4/4) ICC]. In total, 79 of the 207 women in our study tested positive for one or more HPV-HR types, or 38.16%. In the Niari department, 37.5 percent (48/128) of women tested positive for HPV, whereas in the Bouenza department, 39.24 percent (31/79) of women tested positive for HPV. The number of HPV strains infected ranged from two to more than three. There was no statistically significant relationship between sociodemographic factors and genotyping (p>0.05). HPV-HR prevalence, on the other hand, differed greatly depending on cervical cytology (P 0.001). Conclusion: The findings suggest that HPV 16 is more prevalent among women in these two departments of Congo.